Validation of hand motion analysis as an objective assessment tool for the Focused Assessment with Sonography for Trauma examination. Issue 4 (October 2015) - Ziesmann, Markus T.; Park, Jason; Unger, Bertram; Kirkpatrick, Andrew W.; Vergis, Ashley; Pham, Chau; Kirschner, David; Logestty, Sarvesh; Gillman, Lawrence M.
Abstract : BACKGROUND: Point-of-care ultrasonography is a standard part of trauma assessments, but there are no objective tools to assess proficiency and ensure high-quality examinations. Hand motion analysis (HMA) has been validated as a measure of surgical skill but has not previously been applied to ultrasonography. HMA was assessed for construct validity in Focused Assessment with Sonography for Trauma (FAST) performance. METHODS: Two cohorts of 12 expert and 12 novice ultrasonographers performed a FAST examination on a healthy volunteer. Hand motions were recorded with the trakSTAR 3D electromagnetic motion-tracking device (Ascension Technology) and analyzed using our custom-designed Motion Analysis and Recording System (MARS) software. Data were recorded at 240 Hz. Outcomes included time of examination, number of movements, and path length. RESULTS: Time of examination was not different between cohorts (expert, 345.9 seconds; novice, 475.7 seconds; p = 0.12). Total path length of travel was shorter, and the number of discreet movements was less in the expert cohort for the left-hand (18.52 m vs. 28.01 m, p = 0.03, and 109.5 vs. 193.9, p = 0.027, respectively) and the right-hand performance (14.25 m vs. 32.09 m, p < 0.01, and 153.5 vs. 258.5, p = 0.03, respectively) versus the novice cohort. Both total path length traveled and total number of discreet movements were associated with expertise level in logistic regression modeling with areas under the receiver operating characteristic curves of 0.8269 and 0.8205, respectively. CONCLUSION: This is the first study in the medical literature showing HMA as an objective, valid measure of FAST imaging performance. These objective, automated metrics can function as an adjunct measure to assess FAST performance as well as follow progress of and provide feedback to learners to improve future performances. LEVEL OF EVIDENCE: A "diagnostic criteria"–style test where the "diagnosis" is a determination of competence in a care provider, level II. Abstract : Supplemental digital content is available in the text.